The Effect of Guessing Game on Students’ Vocabulary Acquisition at FLC Selong - Usuluddin; Dwimaulani, Astrid; Putri, Nurhidayatika; Wati, Laila (PROJECT (Professional Journal of English Education), 2026)
Vocabulary is an important component in language acquisition, but many beginner students still have difficulty in remembering and using vocabulary in real contexts. Therefore, The objective of the current research is to evaluate how effective the Guessing Game at the Foreign Language Center (FLC) Selong helps students expand their vocabulary in English. This study utilized a quantitative approach with a single group pre-test and post-test design.  20 Level 1 learners that were purposefully chosen made up the research sample. The instrument used was vocabulary tests. According to the findings, students' pre-test average score was 66.50, yet their post-test average score rose to 77.00.  The results of the paired sample t-test revealed a significant difference between the pre-test and post-test, with a significance value (Sig. 2-tailed) of 0.000 <0.05. Thus, it can be concluded that the use of Guessing Game was significantly effective in improving students' mastery of English vocabulary. In addition, students showed a positive response to the game-based learning activities as it was considered fun, lowered anxiety, and increased their confidence in using vocabulary.